The Biological Basis for Nonunions. Issue 6 (14th June 2016) - Brinker, Mark R.; O'Connor, Daniel P.
Abstract : Fracture nonunion is a failure of the biological processes of fracture-healing. Critical cellular events in fracture-healing include the inflammatory response, differentiation and proliferation of progenitor cells, formation of fibrocartilage callus, angiogenesis and subsequent mineralization of the callus, vascular union (restoration of normal medullary circulation), and conversion of woven bone to lamellar bone. All critical events are closely regulated and coordinated by numerous cytokines and growth factors, which are expressed in complex spatial and temporal patterns throughout the repair process. At all phases of fracture-healing, poor cellular and metabolic capacity (e.g., chronic disease), excessive instability, and poor vascularity inhibit cellular responses and healing. Many biological treatments to prevent or treat nonunions are emerging in clinical use, including stem-cell and bone-marrow-aspirate preparations, various progenitor cells and growth factors (e.g., recombinant human bone morphogenetic proteins), and gene therapy.